The Shared Ethical Responsibility of Medically and Non-medically Qualified Experts in Human Drug Development Teams - Kerpel-Fronius, Sandor; Becker, Sander; Barrett, Jane; Brun, Johan; Carlesi, Roberto; Chan, Anthony; Collia, Luis F.; Dubois, Dominique J.; Kleist, Peter; Koski, Greg; Kurihara, Chieko; Laranjeira, Luis F.; et al. (Frontiers in Pharmacology, 2018)
The complexity of developing and applying increasingly sophisticated new medicinal products has led to the participation of many non-medically qualified scientists in multi-disciplinary non-clinical and clinical drug development teams world-wide. In this introductory paper to the “IFAPP International Ethics Framework for Pharmaceutical Physicians and Medicines Development Scientists” it is argued that all members of such multidisciplinary teams must share the scientific and ethical responsibilities since they all influence directly or indirectly both the outcome of the various phases of the medicines development project and the safety of the research subjects involved. The participating medical practitioner retains the overriding responsibility and the final decision to stop a trial if the well-being of the research subjects is seriously endangered. All the team members should follow the main ethical principles governing human research, the respect for autonomy, justice, beneficence and non-maleficence. Nevertheless, the weighing of these principles might be different under various conditions according to the specialty of the members.